Measurement of specific movement power application: evaluation of weight lifters - Funato, K.; Matsuo, A.; Fukunaga, T. (Ergonomics, 2000)
A new dynamometer was developed for the measurement of specific movement power (SMP) exerted by mono- or multi-articular movements. To determine the reproducibility of SMP, two identical test protocols were carried out on separate days for six movement types on seven adult males. The movement types were arm pull (AP), leg rise (LR), knee extension (KE), elbow flexion (EF), hip extension (HE) and squat movement (SQ). Variations in peak power obtained in two tests ranged from 0.7% (AP) to 9.6% (SQ). Coefficients of the test- re-test correlation in peak power ranged from 0.805 (SQ) to 0.961 (AP) and standard errors ranged from 4 W (EF) to 14 W (SQ). SMP in upper extremities increased from 166 W (EF) to 307 W (AP) resulting from the increase in velocity. However, in the movements of lower extremities, SMP increased from 506 W (KE) to 1351 W (SQ) as a result of the increase in force. To evaluate the validity of the SMP, a pull movement in weightlifting was tested and related to the athletic performance on weightlifters. Positive linear correlation (r = 0.862, p < 0.001) was observed between SMP and the total weight best records. It is concluded that this newly developed dynamometer has enough reproducibility and validity for evaluating the SMP, which is developed by various joint movement patterns related to the sport. The feasibility of applying this measuring protocol to the testing and training programmes for improving the daily living activities and athletic performances should now be assessed.